1984
DOI: 10.1126/science.6474162
|View full text |Cite
|
Sign up to set email alerts
|

Neuroleptic-Induced Decrease in Plasma Homovanillic Acid and Antipsychotic Activity in Schizophrenic Patients

Abstract: Plasma-free homovanillic acid, a major metabolite of dopamine, was measured in chronically ill schizophrenic patients both before and during treatment with the antipsychotic phenothiazine, fluphenazine. Neuroleptic treatment was associated with a significant time-dependent decrease in plasma homovanillic acid from pretreatment values, which were significantly elevated when compared with those of age- and sex-matched healthy control subjects. Further, both the absolute concentrations as well as the neuroleptic-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
59
0

Year Published

1986
1986
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 238 publications
(61 citation statements)
references
References 40 publications
2
59
0
Order By: Relevance
“…In fact, preselected and unselected schizotypal individuals, thought to be 'psychosis-prone' (Chapman et al, 1994;Kwapil et al, 1997), perform similar to patients with schizophrenia for cognitive (Gooding et al, 1999;Park, 1999), attentional (Sarkin et al, 1998;Mohr et al, 2003a), behavioral (Barnett and Corballis, 2002;Mohr et al, 2003b) and physiological (Klein et al, 1999;Pizzagalli et al, 2000) measures. Finally, alterations of dopaminergic responsivity may accompany the schizophrenia spectrum disorders in a continuous manner; the DA metabolite homovanillin acid (HVA) correlated with severity of positive symptoms in schizophrenia (Pickar et al, 1984;Davidson and Davis, 1988) and the extent of schizotypal personality disorder (Siever et al, 1991(Siever et al, , 1993. …”
Section: Introductionmentioning
confidence: 99%
“…In fact, preselected and unselected schizotypal individuals, thought to be 'psychosis-prone' (Chapman et al, 1994;Kwapil et al, 1997), perform similar to patients with schizophrenia for cognitive (Gooding et al, 1999;Park, 1999), attentional (Sarkin et al, 1998;Mohr et al, 2003a), behavioral (Barnett and Corballis, 2002;Mohr et al, 2003b) and physiological (Klein et al, 1999;Pizzagalli et al, 2000) measures. Finally, alterations of dopaminergic responsivity may accompany the schizophrenia spectrum disorders in a continuous manner; the DA metabolite homovanillin acid (HVA) correlated with severity of positive symptoms in schizophrenia (Pickar et al, 1984;Davidson and Davis, 1988) and the extent of schizotypal personality disorder (Siever et al, 1991(Siever et al, , 1993. …”
Section: Introductionmentioning
confidence: 99%
“…Despite some argument (Kopin et al 1988;Lambert et al 1993;Maas et al 1988), several lines of investigations have focused on plasma levels of homovanillic acid (pHVA), a major metabolite of DA, for the study of DA-related mental disorders such as schizophrenia based on the assumption that dysfunction in central dopaminergic activity is, to some extent, reflected in this peripheral measure (see Friedhoff and Amin 1997 for review). While conflicting results have been reported regarding differences in pHVA levels between patients with schizophrenia and control subjects (Doran et al 1985;Koreen et al 1994;Maas et al 1993;Pickar et al 1984;Steinberg et al 1993;Sumiyoshi et al 1997a;Whelton et al 1993), there has been accumulated evidence for the association between pHVA levels in schizophrenia and the outcome of neuroleptic treatment (Akiyama et al 1995;Chang et al 1993;Davis et al 1985;Garver et al 1997;Green et al 1993;Nagaoka et al 1997;Sumiyoshi et al 1997b). …”
mentioning
confidence: 99%
“…Interactions between the two systems have been well studied in the CSF and plasma of schizophrenic patients through their respective metabolites: the dopamine metabolite homovanillic acid (HVA) and the norepinephrine metabolite 3-methoxy-4-hydroxyphenylglycol (MHPG). Plasma HVA has been shown to reflect central or brain dopamine activity through studies in animals and humans (Bacopoulos et al 1979;Kendler et al 1982;Maas et al 1993;Lambert et al 1993;Amin et al 1992), indicating that 11-35% of plasma HVA comes from the brain.Several studies of schizophrenia have noted that the behavioral response to antipsychotic drugs (i.e., a decrease in psychosis levels) parallels a decrease in plasma HVA levels in schizophrenic patients over time (Pickar et al 1984(Pickar et al , 1986Davidson and Davis 1988;Davila et al 1988;Mazure et al 1991;Sharma et al 1989). Some studies have reported an initial increase in plasma HVA in the first week of antipsychotic drug From the VA Pittsburgh Healthcare System (MEK, JKY, DPvK), Pittsburgh, Pennsylvania; and Western Psychiatric Institute and Clinic (JKY, DPvK), University of Pittsburgh, School of Medicine, Pittsburgh, Pennsylvania.…”
mentioning
confidence: 99%
“…Several studies of schizophrenia have noted that the behavioral response to antipsychotic drugs (i.e., a decrease in psychosis levels) parallels a decrease in plasma HVA levels in schizophrenic patients over time (Pickar et al 1984(Pickar et al , 1986Davidson and Davis 1988;Davila et al 1988;Mazure et al 1991;Sharma et al 1989). Some studies have reported an initial increase in plasma HVA in the first week of antipsychotic drug From the VA Pittsburgh Healthcare System (MEK, JKY, DPvK), Pittsburgh, Pennsylvania; and Western Psychiatric Institute and Clinic (JKY, DPvK), University of Pittsburgh, School of Medicine, Pittsburgh, Pennsylvania.…”
mentioning
confidence: 99%
See 1 more Smart Citation